Pengaruh Akupresure Kombinasi Inhalasi Aromaterapi Lemon Terhadap Pengurangan Frekuensi Mual Muntah Pada Ibu Hamil Trimester 1 - Yuni Subhi Isnaini; Sestu Iriami Mintaningtyas (Universitas Malahayati Lampung, 2022)
ABSTRACT Nausea and vomiting are physiological adaptations of the pregnancy process caused by changes in the endocrine system in primigravida around 60-80% and multigravida 40-60%. The increase in Chorionic Gonadotropin Hormone (HCG) with the highest levels usually occurs in the first trimester period, namely in the first 12-16 weeks of pregnancy. During pregnancy, unwanted problems can occur. Several non-pharmacological therapeutic approaches to reduce nausea and vomiting in pregnancy are Acupressure, a combination of Lemon Aromatherapy Inhalation. The purpose of this study was to evaluate the effect of Acupressure combination of Inhaled Lemon Aromatherapy on the frequency of nausea and vomiting in first trimester pregnant women in SP IV Public Health Center Prafi District, Manokwari Regency. This study conducted an analysis of the frequency of nausea and vomiting after being given Acupressure with a combination of Lemon Aromatherapy Inhalation. This type of research is a quasi-experimental research with Pre-Post test research design with control group. The sample in this study were pregnant women who experienced nausea and vomiting in the first trimester in the SP IV Health Center Work Area, Prafi District, as many as 42 respondents with the sampling technique using purposive sampling. This study conducted an analysis of the frequency of nausea and vomiting in pregnant women before and after being given the Inhaled Lemon Aromatherapy Combination Acupressure intervention for a duration of 30 times 5-10 minutes, the intervention was carried out for 7 days according to the Acupressure combination Inhaled Lemon Aromatherapy SOP. The research instrument used was the PUQE questionnaire. The data taken are primary data and data analysis using parametric and non-parametric tests. The results showed that there were differences in the frequency of nausea and vomiting scores before and after treatment in the intervention group with p value value (0.05) and there was no difference in the frequency of nausea and vomiting scores before and after treatment in the control group with p value value. (0.05). The conclusion is that the combination of Inhaled Lemon Aromatherapy Acupressure has an effect on the frequency of nausea and vomiting in pregnant women in the first trimester after being given the intervention. Keywords: Pregnant Women, Frequency of Nausea Vomiting, Acupressure Combination of Lemon Aromatherapy Inhalation. ABSTRAK Mual dan muntah merupakan adaptasi fisiologis proses kehamilan yang disebabkan adanya perubahan sistem endokrin pada primigravida sekitar 60-80% dan multigravida 40-60%. Peningkatan Hormon Chorionic Gonadotropin (HCG) dengan kadar tertinggi biasanya terjadi pada periode trimester I yaitu di usia kehamilan 12-16 minggu pertama. Masa kehamilan dapat terjadi masalah- masalah yang tidak diinginkan. Beberapa pendekatan Terapi non farmakologis untuk mengurangi mual muntah pada kehamilan yaitu dengan Akupressure kombinasi Inhalasi Aromaterapi Lemon. Tujuan dari penelitian ini adalah untuk mengevaluasi pengaruh Akupressure kombinasi Inhalasi Aromaterapi Lemon terhadap frekuensi mual muntah Pada Ibu Hamil Trimester I Di Wilayah Kerja Puskesmas SP IV Distrik Prafi Kabupaten Manokwari. Penelitian ini melakukan analisis frekuensi mual muntah setelah diberikan Akupressure kombinasi Inhalasi Aromaterapi Lemon. Jenis penelitian ini adalah penelitian quasy experiment dengan rancangan penelitian Pre-Post test with control group. Sampel dalam penelitian ini adalah ibu hamil yang mengalami mual muntah Trimester I di Wilayah Kerja Puskesmas SP IV Distrik Prafi sebanyak 42 responden dengan teknik pengambilan sampel menggunakan purposive sampling. Penelitian ini melakukan analisis frekuensi mual muntah pada ibu hamil sebelum dan setelah diberikan intervensi Akupressure kombinasi Inhalasi Aromaterapi Lemon durasi 30 kali 5-10 menit intervensi dilakukan selama 7 hari sesuai SOP Akupressure kombinasi Inhalasi Aromaterapi Lemon. Instrumen penelitian yang digunakan adalah kuesioner PUQE. Data yang diambil merupakan data primer dan analisa data menggunakan uji parametrik dan non parametrik test. Hasil penelitian menunjukan bahwa terdapat perbedaan skor frekuensi mual muntah sebelum dan sesudah perlakuan pada kelompok intervensi dengan nilai p value nilai α (0,05) dan tidak terdapat perbedaan skor frekuensi mual muntah sebelum dan sesudah perlakuan pada kelompok kontrol dengan nilai p value nilai α (0,05). Kesimpulan yaitu Akupressure kombinasi Inhalasi Aromaterapi Lemon berpengaruh terhadap frekuensi mual muntah pada ibu hamil trimester I setelah diberikan intervensi.Kata kunci: Ibu Hamil, Frekuensi Mual Muntah, Akupressure kombinasi Inhalasi Aromaterapi Lemon.